2010
DOI: 10.1111/j.1095-8649.2010.02607.x
|View full text |Cite
|
Sign up to set email alerts
|

Shoaling preference and evidence for maintenance of sibling groups by juvenile black perch Embiotoca jacksoni

Abstract: Group sizes in free-living juvenile black perch Embiotoca jacksoni were quantified and predictions of the hypothesis that such groups comprise sibling brood-mates were tested. Group sizes in the field were within the range of female brood sizes and often occurred close to each other but did not merge. In captivity, juveniles formed groups immediately after birth. In laboratory experiments, they also associated significantly more with chambers containing familiar members of their own brood than empty chambers b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…A handful of studies have found spatiotemporal kin association in the aquatic environment (Planes et al 1993;Olsén et al 2004;Selkoe et al 2006;Miller-Sims et al 2008;Buston et al 2009;Sikkel and Fuller 2010). Over half these studies found high levels of relatedness among fish within discrete aggregations (Miller-Sims et al 2008;Olsén et al 2004;Sikkel and Fuller 2010). This level of association has been demonstrated in the demersal livebearing black perch, Embiotoca jacksoni (Sikkel and Fuller 2010), the benthic nesting humbug damselfish, Dascyllus aruanus (Buston et al 2009), the midwater aggregate spawning kelp bass, Paralabrax clathratus (Selkoe et al 2006), and the riverine benthic nesting Atlantic salmon, Salmo salar (Olsén et al 2004).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A handful of studies have found spatiotemporal kin association in the aquatic environment (Planes et al 1993;Olsén et al 2004;Selkoe et al 2006;Miller-Sims et al 2008;Buston et al 2009;Sikkel and Fuller 2010). Over half these studies found high levels of relatedness among fish within discrete aggregations (Miller-Sims et al 2008;Olsén et al 2004;Sikkel and Fuller 2010). This level of association has been demonstrated in the demersal livebearing black perch, Embiotoca jacksoni (Sikkel and Fuller 2010), the benthic nesting humbug damselfish, Dascyllus aruanus (Buston et al 2009), the midwater aggregate spawning kelp bass, Paralabrax clathratus (Selkoe et al 2006), and the riverine benthic nesting Atlantic salmon, Salmo salar (Olsén et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, sharks born in the same location may simply be found together over time because they are similarly associated with their natal habitat. A handful of studies have found spatiotemporal kin association in the aquatic environment (Planes et al 1993;Olsén et al 2004;Selkoe et al 2006;Miller-Sims et al 2008;Buston et al 2009;Sikkel and Fuller 2010). Over half these studies found high levels of relatedness among fish within discrete aggregations (Miller-Sims et al 2008;Olsén et al 2004;Sikkel and Fuller 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a prior study suggests that the degree of crowding within a population may be related to genetic diversity. In a set of laboratory experiments, Sikkel and Fuller () found that juvenile black surfperch have a very strong preference for schooling with close relatives (broodmates) over unrelated individuals of the same size and age. These results imply that all else equal, populations with lower genetic diversity and greater average relatedness should experience a greater degree of crowding.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, test fishes are not only related to, but are also familiar with the stimulus fishes (having previously been housed together or reared together in utero). Many studies have been unable to discount this straightforward explanation (see discussions in Quinn & Hara 1986;Winberg & Olsén 1992;Brown & Brown 1996a;Griffiths & Magurran 1999;Steck et al 1999;Krause et al 2000;Hain & Neff 2007;Sikkel & Fuller 2010). Indeed, Courtenay et al (1997) and more recently Frommen et al (2007a) found that common rearing increased the preference for siblings among juvenile coho salmon and three-spined sticklebacks, respectively.…”
Section: Evidence For Kin Recognition From Laboratory Studiesmentioning
confidence: 98%